Activatable Near‐Infrared Probe for Fluorescence Imaging of γ‐Glutamyl Transpeptidase in Tumor Cells and In Vivo. Issue 59 (18th August 2017) - Luo, Zhiliang; Feng, Liandong; An, Ruibing; Duan, Guanfu; Yan, Runqi; Shi, Hua; He, Jian; Zhou, Zhengyang; Ji, Changge; Chen, Hong‐Yuan; Ye, Deju
Abstract: γ‐Glutamyl transpeptidase (GGT) is a cell‐membrane‐bound enzyme that is involved in various physiological and pathological processes and is regarded as a potential biomarker for many malignant tumors, precise detection of which is useful for early cancer diagnosis. Herein, a new GGT‐activatable near‐infrared (NIR) fluorescence imaging probe (GANP) by linking of a GGT‐recognitive substrate γ‐glutamate (γ‐Glu) and a NIR merocyanine fluorophore (mCy‐Cl) with a self‐immolative linker p ‐aminobenzyl alcohol (PABA) is reported. GANP was stable under physiological conditions, but could be efficiently activated by GGT to generate ≈100‐fold enhanced fluorescence, enabling high sensitivity (detection limit of ≈3.6 mU L −1 ) and specificity for the real‐time imaging of GGT activity as well as rapid evaluation of the inhibition efficacy of GGT inhibitors in living tumor cells. Notably, the deep tissue penetration ability of NIR fluorescence could further allow GANP to image GGT in frozen tumor tissue slices with large penetration depth (>100 μm) and in xenograft tumors in living mice. This GGT activatable NIR fluorescence imaging probe could facilitate the study and diagnosis of other GGT‐correlated diseases in vivo. Abstract : A γ‐glutamyl transpeptidase (GGT) activatable NIR fluorescence probe (GANP) was developed, allowing for real‐time imaging of endogenous GGT activity both in tumor cells and living mice with high sensitivity and specificity.